Mirrors in Russian Women’s Autobiographical Writing: The Self Reflected in Works by Alla Demidova and Vera Luknitskaia - Karin Sarsenov (Studies in 20th & 21st Century Literature, 2010)
In autobiographical writing, the mirror is not only a privileged metaphor for the genre as a whole; it also functions as a primary administrator of boundaries, demarcating the space of the self from the foreign, the chaotic, and the unknown. The mirror metaphor is not gender neutral: in Western elite culture the mirror has served to reinforce the patriarchal dichotomy between man/mind and woman/body, prompting Luce Irigaray’s view of the mirror as “a male-directed instrument of literal objectification.” This article examines two women-authored texts in which the mirror motif is fundamental to the construction of the autobiographical self: the actress Alla Demidova’s The Flying Line of Memory (2000) and the literary scholar Vera Luknitskaia’s Ego – Echo (2003). A close reading of the texts maps out the operations performed by the mirror and locates the boundaries delineated. The reading shows that the two authors are united by the fervency with which they affirm their social identity as members of the intelligentsia. Their gendered identity is expressed in terms of vulnerability, implicitly in Demidova, by the omission of all intimate detail, and explicitly in Luknitskaia, in reports of sexual assault. However, both have omitted one of the most frequently encountered uses of the mirror motif in European culture—to connote female vanity. In their work, the mirror is a productive literary device, affirming the feminine self.
Keywords: autobiographical writing; autobiography; woman/body; man/mind; feminism; mirror metaphor; Luce Irigaray; women authors; autobiographical self; Alla Demidova; The Flying Line of Memory; Vera Luknitskaia; Ego – Echo; social identity; gendered identity; feminine self